Implementasi Kebijakan Rekam Medis Elektronik Di Rumah Sakit Umum Daerah Provinsi Banten - Amiruddin, Suwaib; Eka, Novitran; Ema Jumiati, Ipah (Universitas Serang Raya, 2024)
This study focuses on the Implementation of Electronic Medical Record Policy at Banten Regional General Hospital. The purpose of the study was to determine the Implementation of Electronic Medical Record Policy at Banten Regional General Hospital. Implementation of the policy from George C Edward III, namely communication, resources, disposition and bureaucratic structure. The research method used is a qualitative descriptive method. Data validity test using source triangulation and member check techniques. Data analysis using Miles and Huberman qualitative data analysis. The results of the study are known (1). Communication of the Electronic Medical Record policy is still less than optimal as indicated by minimal socialization and minimal training. (2). The resources of the Electronic Medical Record policy are quite optimal as indicated by the existence of a budget, quality health services (3). The disposition of the Electronic Medical Record policy is less than optimal as indicated by the weak quality of the internet network and the lack of servers from Banten Regional General Hospital (4). The bureaucratic structure of the Electronic Medical Record policy is less than optimal as indicated by minimal supervision and periodic evaluation. Keywords: Policy Implementation, Electronic Medical Records, Banten Regional Hospital.